PENGARUH RISIKO KEUANGAN, NILAI PERUSAHAAN, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP PRAKTIK PERATAAN LABA : STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BEI - VIDYA RIADIANTO, DITO (Jurnal Akuntansi AKUNESA, 2016)
This research examines whether Financial Risk, Firm Value, Company Size, and Profitability affect income smoothing listed on the Indonesia Stock Exchange. Smoothing eranings is difined as the manner used by management to reduce fluctuations in reported eranings either artificially (through the method of accounting) as well as in real Ithrough the transaction). Earnings smoothing action has been considered a common action. Smoothing profits made by managers to reduce the fluctuations of reported earnings and increase the ability of investors to forecast future cash flows. The purpose of this research is to test empirically the influence of profitability, financial risk, the value of the company, the ownership structure, firm size and industry type of smoothing earnings in companies listed on the Indonesia Stock Exchange. This study population is a publicly traded company listed on the Stock Exchange in the year 2010-2014 as many as 10 companies. Determination of the sample in this study carried out purposive sampling. Samples were taken some 10 companies. Tools of analysis used logistic regression (Logistic Regression). Based on this research can be concluded : Financial risks and a significant positive effect on earnings smoothing and H1 received. Firm Value had no effect on earnings smoothing and H2 is rejected. Company Size and a significant positive effect on earnings smoothing and H3 received. Profitability and a significant positive effect on earnings smoothing and H4 received.